Avoiding the Deadly Sins of Humanitarian Missions: How to Do Good Better. (2nd September 2014) - McMains, Kevin C.; Isaacson, Glenn C.; Netterville, James L.; Wagner, Richard
Abstract : Program Description: Humanitarian surgical trips provide an opportunity to deliver care that would otherwise be unavailable. However, there is significant variability among humanitarian missions. This variability has contributed to some unfortunate patient outcomes. This miniseminar will explore "deadly sins" common to medical humanitarian efforts and issues that are unique to surgical humanitarian missions. Panelists with extensive humanitarian experience will discuss available data and areas with a lack of data concerning humanitarian efforts. Best practices will be discussed with respect to appropriate standard of care, duration, follow‐up, research, role of the media, and integration with local care systems. Educational Objectives: (1) Critically evaluate the existing literature and identify gaps in knowledge regarding humanitarian efforts in otolaryngology. (2) Recognize "best practices" including appropriate standard of care, duration, follow‐up, conduct of research, role of the media, and integration with local care systems. (3) Critically evaluate and devise methods to improve existing humanitarian efforts in otolaryngology.